Metabolic tumor burden is associated with major oncogenomic alterations and serum tumor markers in patients with resected pancreatic cancer. Issue 2 (1st May 2015) - Shi, Si; Ji, Shunrong; Qin, Yi; Xu, Jin; Zhang, Bo; Xu, Wenyan; Liu, Jiang; Long, Jiang; Liu, Chen; Liu, Liang; Ni, Quanxing; Yu, Xianjun
Highlights We analyzed the correlation between metabolic tumor burden and the major oncogenomic alterations in pancreatic cancer. We identified the linear correlation between serum tumor markers and metabolic tumor burden. We established equations for MTV and TLG using CA19-9 and CA125 as independent variables.